Regulation of caspase-3 expression to maintain fetal growth in Porphyromonas gingivalis-infected pregnant rats - Banun Kusumawardani; Yuliana MD Arina; Azham Purwandhono (Journal of Dentomaxillofacial Science, 2016)
Periodontal disease has been involved in a variety of systemic disorders and suspected as a potential risk factor for fetal growth restriction. Periodontal pathogenic bacteria may actively regulate embryonic development, implantation and placental trophoblast cell invasion. This study aimed to analyze the role of TNF-α, IL-10 and caspase-3 to maintain fetal growth in Porphyromonasgingivalis-infected pregnant rats. Female rats were infected with live-Porphyromonas gingivalis at concentration of 2x109 cells/ml into subgingival sulcus area of the maxillary first molar before and during pregnancy. They were sacrificed on gestational day (GD)-14 and GD20. The weight and length of placentas and fetuses were evaluated. The expression of TNF-α, IL-10 and caspase-3 in macrophages and trophoblast cells were detected by immunohistochemistry. On GD14, TNF-α (R2=0.416;P=0.000) and IL-10 (R2=0.187;P=0.012) had an important role to increase expression of caspase-3 in the placenta, but only TNF-α (R2=0.393;P=0.000 ) was able to increase the expression of caspase-3 on GD20. TNF-α and caspase-3 also had an important role (P<0.000) to decrease fetal weight, fetal length and placental weight on GD14 and GD20, but it was not the case with IL-10 (P>0.000). The increasing expressions of TNF-α and IL-10 did not only enhance immune protection, but also maintained the trophoblast cells survival by regulating expression of caspase-3. Porphyromonas gingivalis infection in maternal periodontal tissue can lead to decrease in placental weight, fetal weight and fetal length which mediated by increasing expression of TNF-α, IL-10 and caspase-3 in the placenta.